2006
DOI: 10.1016/j.ijsu.2006.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor augments the healing of demineralized bone matrix grafts

Abstract: VEGF+DBM(IM) powder is a promising graft material, and warrants further clinical investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 22 publications
0
15
0
1
Order By: Relevance
“…Because PEDF is known as a potent antiangiogenic factor its expression in bone would have undesirable consequences. Previous reports showed that VEGF can have a direct effect on osteoblast differentiation and bone mineralization [19,20,26]. VEGF plays important role in fracture healing through coupled angiogenesis and osteogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Because PEDF is known as a potent antiangiogenic factor its expression in bone would have undesirable consequences. Previous reports showed that VEGF can have a direct effect on osteoblast differentiation and bone mineralization [19,20,26]. VEGF plays important role in fracture healing through coupled angiogenesis and osteogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF is a known key mediator of angiogenesis and has roles in both bone-forming processes -direct (intramembranous) and indirect (endochondral ossification) (Emad et al 2006, Dai & Rabie 2007, Li et al 2009). Highlighting VEGF's essential role during bony repair, Street et al (2002) found that in a mouse bone fracture model, the absence of VEGF delayed bone formation by halting the initial soft callus from being converted into hard bony callus.…”
Section: Potential Changes At the Adjacent Non-injured Region Of The mentioning
confidence: 99%
“…Intramembranous bone formation also depends on VEGF signaling. Blocking the VEGF receptors, VEGFR1 and VEGFR2, with neutralizing antibodies decreased blood vessel formation and bone regeneration (15), while administering exogenous VEGF increased formation of mineralized bone within bone defects (14,16,17). In addition, VEGF regulates maturation and differentiation of osteoclasts and, thus, is necessary for maintenance of normal bone remodeling (14,18,19).…”
Section: Introductionmentioning
confidence: 99%